Designing and orchestrating the classroom experience for technology-enhanced embodied learning - Ioannou, Marianna; Ioannou, Andri; Georgiou, Yiannis; Retalis, Symeon (My University, 2020)
The concepts of embodiment and embodied learning, deeply rooted in theories of embodied cognition, are gaining traction in the field of education. New and affordable educational technologies (e.g., motion-based technologies, AR, VR) enable researchers and practitioners to include more gestures and body movements into their learning designs. Yet, while technology-enhanced embodied learning shows positive results during controlled trials in laboratory settings or one-to-one interventions in special classrooms or units, findings are dissimilar when relevant implementations are conducted in mainstream school classrooms. This paper presents the first stage of a design-based research study aiming at implementing an orchestration strategy for technology-enhanced embodied learning, guided by an already published conceptual framework on classroom orchestration. With this study we aim to spark the dialog on classroom orchestration strategies for the successful enactment of technology-enhanced embodied learning in the classroom, highlighting the essential need to consider learning design as it is not a simple process to shift laboratory success to real world learning.
Keywords: Computer science; Engineering education; Embodied cognition; Learning designs; Real-world learning; VR; AR